Agents of their own emancipation: manumission of slaves in Lima - Aguirre, Carlos (1991)
​By combining the analysis of 1,298 letters of manumission registered in Lima between 1840 and 1854, and information from numerous cases of litigation and negotiation between masters and slaves, this article questions previous interpretations in the sense that, 1) the abolition of slavery was either something enforced from the outside or a grace from Castilla, and 2) that the slaves had neither the interest on their freedom nor the capacity for challenging the power of their masters. The picture emerging from this study is one of a great pugnacity in the pursue of their freedom, the use of a variety of strategies for achieving their goals, and the evidence that the disintegration of slavery in Peru was, to a great extent, the result of the many forms of slave resistance.